1993
DOI: 10.1111/j.1439-0523.1993.tb01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Resistance to the Russian Wheat Aphid in Hexaploid Wheat

Abstract: The Russian wheat aphid (RWA), Diuraphis noxia (Mordvilko), poses a serious threat to wheat {Triticum aestivum L.) production in many parts of the world. This research was initiated to evaluate wheat accessions for detection of resistance to the RWA. Over 12,000 wheat cultivars and plant introductions (Pis) from the USD A-ARS National Small Grains Gollection were evaluated for reaction to RWA feeding damage. Twenty-nine Pis from Iran, Afghanistan, and the former Soviet Union, of various agronomic backgrounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Wheat cereal introduction 2401 (CI2401) from Tajikistan was resistant to the original biotype (RWA1) (Porter et al 1993(Porter et al , 2005. After the appearance of RWA2, Collins et al (2005a) screened 761 germplasm accessions previously determined to be resistant to RWA) and showed that CI2401 also has resistance to RWA2.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat cereal introduction 2401 (CI2401) from Tajikistan was resistant to the original biotype (RWA1) (Porter et al 1993(Porter et al , 2005. After the appearance of RWA2, Collins et al (2005a) screened 761 germplasm accessions previously determined to be resistant to RWA) and showed that CI2401 also has resistance to RWA2.…”
Section: Introductionmentioning
confidence: 99%
“…This result reflects the Mediterranean and/or Asian regions as the probable source of RWA resistance in U.S. germplasm. Porter et al (1993) reported that of 12,000 cultivars and introductions screened for RWA response, all the resistant lines identified came from these regions. Sub-cluster Ia consisted of 21 RWA accessions predominantly resistant to both biotypes, and 20 of them came from Iran.…”
Section: Resultsmentioning
confidence: 99%
“…Most originate in eastern Mediterranean and Asian regions where RWA is endemic, including Turkey, Syria, Iran, Afghanistan, and southern regions of the former Soviet Union (Porter et al 1993;Collins et al 2005). Porter et al (1993) reported that of 12,000 wheat cultivars and plant introductions (PI) screened for RWA, only 29 had moderate to high levels of resistance and all are from Mediterranean and Asian regions. This observation indicates low genetic diversity for wheat breeding for resistance to RWA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, primary screening is necessary to classify the varieties resistant to the aphids through artificial infection of plantlets by aphids in the greenhouse (Porter et al 1993;Tolamy et al 1999). In this study, at the two-to three-leaf stage of development, plants were transported to a growth chamber at a temperature of 20 ± 1°C, 60 ± 5% RH and 14:10 (L:D) h to perform the experiment.…”
Section: Laboratory Screeningmentioning
confidence: 99%